Front Cover: Atomic Layer Deposition of Space‐Efficient SnO2 Underlayers for BiVO4 Host–Guest Architectures for Photoassisted Water Splitting (ChemSusChem 9/2019). Issue 9 (2nd May 2019) - Lamm, Benjamin; Zhou, Lite; Rao, Pratap; Stefik, Morgan
Abstract : The Front Cover shows SnO2 as an effective underlayer for the photoelectrochemical (PEC) water splitting on bismuth vanadate (BiVO4 ), a promising oxide for water splitting. It is often prepared with a host–guest architecture and an underlayer that limits charge recombination at the host–guest interface. Despite widespread use of underlayers relatively little is understood about how the underlayer materials chemistry affects the resulting performance. This is particularly important for host–guest architectures where the short transport paths needed for high PEC efficiency provide a high interfacial area for recombination. To mitigate blocking of pore volume by the interlayer, a very thin SnO2 of only 8 nm (usually 60–80 nm) is prepared by atomic layer deposition, giving rise to improved space efficiency. More information can be found in the Full Paper by B. Lamm et al. onpage 1916 in Issue 9, 2019 (DOI:10.1002/cssc.201802566 ).